planta trangênica transformada com um vetor de expressão, semente, vetor de expressão, e, método para produzir uma planta trangênica resistente a nematóides - DASHARATH PRASAD LOHAR; STEVEN HILL (2015)
The invention provides nematode-resistant transgenic plants and seed comprising polynucleotides encoding Medicago truncatula cysteine cluster proteins which comprise no more than four cysteine residues in the respective mature peptides. The invention also provides methods of producing transgenic plants with increased resistance to soybean cyst nematode and expression vectors for use in such methods.